2022
DOI: 10.3390/molecules27030885
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis of Mycobacterium tuberculosis RpoB Drug-Resistant Clinical Mutations on Rifampicin Drug Binding

Abstract: Tuberculosis (TB), caused by the Mycobacterium tuberculosis infection, continues to be a leading cause of morbidity and mortality in developing countries. Resistance to the first-line anti-TB drugs, isoniazid (INH) and rifampicin (RIF), is a major drawback to effective TB treatment. Genetic mutations in the β-subunit of the DNA-directed RNA polymerase (rpoB) are reported to be a major reason of RIF resistance. However, the structural basis and mechanisms of these resistant mutations are insufficiently understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…RIF has an effectiveness of about 95% in cases of TB caused by susceptible strains [ 47 ], with a daily oral administration of the standard 600 mg single dose [ 24 , 48 ] or of a dose corresponding to 10–20 mg RIF/kg body weight [ 49 , 50 ]. Alone or in combination with other drugs, it represents the main treatment for infections (produced by various microorganisms), such as TB ( Mycobacteria tuberculosis ), osteomyelitis ( Staphylococcus aureus ), meningococcal disease ( Neisseria meningitidis ), leprosy ( Mycobacterium leprae ), gonorrhea ( Neisseria gonorrhoeae ) [ 51 ], Legionnaire’s disease ( Legionella pneumophila) [ 19 , 28 ] and even HIV [ 52 , 53 ]. Under regulated dosage, RIF is also recommended against methicillin-resistant Staphylococcus aureus [ 19 ], to treat cholestatic pruritus and infections associated with prosthetic joints [ 54 ], such as chemoprophylaxis of the postoperative endophthalmitis [ 55 ], or against Brucellosis and meningitis caused by Streptococcus pneumoniae , Haemophilus influenzae Type b and Neisseria meningitides [ 19 ].…”
Section: Rifamycins—properties and Clinical Treatmentmentioning
confidence: 99%
“…RIF has an effectiveness of about 95% in cases of TB caused by susceptible strains [ 47 ], with a daily oral administration of the standard 600 mg single dose [ 24 , 48 ] or of a dose corresponding to 10–20 mg RIF/kg body weight [ 49 , 50 ]. Alone or in combination with other drugs, it represents the main treatment for infections (produced by various microorganisms), such as TB ( Mycobacteria tuberculosis ), osteomyelitis ( Staphylococcus aureus ), meningococcal disease ( Neisseria meningitidis ), leprosy ( Mycobacterium leprae ), gonorrhea ( Neisseria gonorrhoeae ) [ 51 ], Legionnaire’s disease ( Legionella pneumophila) [ 19 , 28 ] and even HIV [ 52 , 53 ]. Under regulated dosage, RIF is also recommended against methicillin-resistant Staphylococcus aureus [ 19 ], to treat cholestatic pruritus and infections associated with prosthetic joints [ 54 ], such as chemoprophylaxis of the postoperative endophthalmitis [ 55 ], or against Brucellosis and meningitis caused by Streptococcus pneumoniae , Haemophilus influenzae Type b and Neisseria meningitides [ 19 ].…”
Section: Rifamycins—properties and Clinical Treatmentmentioning
confidence: 99%
“…The clinical effects of H451D, H451L, H451N and H451R were also reported through several studies encompassing multiple populations worldwide [ 28 ]. Several in silico studies have attempted to investigate the binding of RIF at the Mtb -RNAP β subunit, thus providing mechanistic insights into the delimiting effects of these mutations [ 29 , 30 , 31 , 32 ]. Some specifically revealed that D441V, H451D, H451R and H451Y mutations may affect RIF activity by altering the critical binding pocket interactions [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several in silico studies have attempted to investigate the binding of RIF at the Mtb -RNAP β subunit, thus providing mechanistic insights into the delimiting effects of these mutations [ 29 , 30 , 31 , 32 ]. Some specifically revealed that D441V, H451D, H451R and H451Y mutations may affect RIF activity by altering the critical binding pocket interactions [ 29 , 30 , 31 , 32 ]. Moreover, although numerous RRDR and non-RRDR or distal Mtb -RNAP mutations have been reported, the majority of clinical cases of RIF inefficacy have been linked to high-confidence mutations mostly occurring at residue positions D441, H451 and S456 located within RRDR cluster I [ 28 ].…”
Section: Introductionmentioning
confidence: 99%